Novels of Kamala Markandaya – a Critical Study: Exploring the portrayal of women in the novels of Kamala Markandaya (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Indian women novelists inEnglish have been presenting woman as the centre of concern in their novels.